Making sense of line graph / Kin Eng Chin, Fui Fong Jiew and Johan @ Eddy Luaran - Chin, Kin Eng; Jiew, Fui Fong; Luaran, Johan @ Eddy (Universiti Teknologi MARA, 2025)
Line graphs serve as visual representations of quantitative information, aiding readers in comprehending extensive data, trends, and relationships. Given their widespread use in daily life, it is expected that everyone can make sense of line graphs. This paper proposes and validates a sensemaking perspective, and it reports on the ways mathematics undergraduates make sense of a contextbased line graph. Data were collected through a line graph task and semi-structured interviews. The findings indicate that the mathematics undergraduates made sense of the graph through perception, operation, and reason. This paper contributes insights into how the participants make sense of the line graph and offers evidence that can inform researchers, educators and curriculum developers about the validity of the framework. This framework can serve as a useful tool for future research in similar areas and potentially shape instructional approaches.